THE EFFECTIVENESS OF CREATIVE WRITING ON STUDENTS’ DESCRIPTIVE PARAGRAPH WRITING ABILITY AT THE ELEVENT GRADE STUDENTS OF SMAN 11 PALEMBANG - Keke Yamona Bastion; Evi Rosmiyat; Ana Theriana (CV. Fahr Publishing, 2023)
The title of this study is The Effectiveness of Creative Writing on Students’ Descriptive Paragraph Writing Ability at the Elevent Grade Students of SMAN 11 Palembang. The formulation of this study the effectiveness of creative writing on descriptive paragraphs against the writing abilities of students in class XI SMAN 11 Palembang. The writer used a pretest-posttest consisting of an experimental class and a control class, meaning the writer selected the group to be randomly studied to find out the differences between the two groups. Students of Class XI IPS 3 and XI IPS 4 are selected classes to be used as samples, each consisting of 35 students. The data collected was taken from a written test. The average pre-test score for the experimental class was 64.25, whereas the post test score was 70.08, as well as the average pretest score in the control class was 63.51 while the posttest score was 64,00. Results from the two groups above showed a positive response to the student’s ability to write descriptive paragraphs. The results of this research showed that creative writing on student writing ability had a low score at the time of the pretest. After treatment, student writing ability improved significantly. It can be seen from higher student scores than before. Data from the writing test had a positive result against student creative writing in their writing ability. Keywords:Creative writing, descriptive paragraph, writing ability